Una antorcha que necesita mantenerse en alto - Bécquer Águila, Jorge Luis (Revista Cubana de Estomatología, 2014)
Recently the Cuban Society of Stomatology, in the framework of the National Symposium «Vision Oral Health», held the II Workshop on Oral Cancer, in greeting on December 5, declared internationally by the Latin American Dental Federation (FOLA) as a day of struggle against that pathological entity throughout this region. This date was coincided with that of the onomastics of the illustrious Cuban scientist Dr. Julio César Santana Garay, in recognition of all the work he has done in this field. A set of contextual factors has enabled Cuba to comprehensively address the prevention of this disease, and direct it to selected groups as well as to the population in general. First, since the 1960s (the 20th century), the Cuban public health system provides free, accessible and universal medical and dental care through a coordinated national network of primary, secondary and tertiary services. This continuous attention is guaranteed by the Cuban constitution, and protects the right of people to receive adequate medical and dental care. Second, the Cuban health approach is based on the principle that the prevention of diseases allows a more effective use of resources than the treatment of them once they manifest themselves. In Cuba, massive programs and campaigns have been developed, but the success has been in popular participation and we are all people. In general, these programs and campaigns have a biosychosocial focus, and not only an epidemiological one, so they consider a set of factors that create vulnerability and risks, as in the case of oral cancer. Finally, the political will of the Ministry of Public Health and the Cuban government allows the establishment of interdisciplinary and intersectoral programs that are fundamental for the achievement and maintenance of the health of the population. To this end, the National Program for the Prevention of Oral Cancer was created, and the intention is for it to work, but this requires awareness, not only of stomatologists, but of each directive, of any organization and institution that is capable of carrying out the work as an important mission. Transmit information, clarify the aspects that may disturb people, work on community intervention projects that arrive in a simple and accessible way to local actors and decision-makers, making viable the management of some basic technical elements for those who wish to work with seriousness and rigor in this field, it may not be an easy task for someone who is defeated before trying such a noble task. On the contrary, whoever recognizes the work that others like Dr. Santana have started, who has the professional ethic and the humanistic principles to carry out this worthy task, will not let the torch go out. Health promotion, prevention tasks, active research, the creation of educational materials, the inclusion and prioritization of the topic in various family and social spaces, the identification of problems, the design of strategies, and their evaluation, they can not be left on anyone's land, nor should they weigh on just a couple of shoulders. It is time to jump to an upper echelon, where true science reaches the population and is realized within it with real understanding and extensive participation of experts and affections. It is time to propitiate that the dynamic overcomes the aesthetic, and that the totality implicitly involves the participation of all parties. It is necessary that science does not leave behind training or research, as the human should not forget the support and accompaniment. There are no recipes or easy answers, but the Oral Cancer Detection Program (PDCB) and its methodology put Cuba in an advantageous position before those countries with a lack of political will to solve health problems, with inadequate access to services of prevention and treatment, and in general with an inadequate and unbalanced infrastructure. The fact of being a reference in Latin America is a challenge, and to face it we need to identify evidences regarding the pathogenesis, to carry out more preventive actions, to exchange opinions regarding the progress of the Program in our country, to undertake strategies in the search for greater effectiveness, and assimilate experiences that make us grow a little more in the direction of success.